Sexwise Comparison and Evaluation of Carcass Traits in Indigenous Chicken - Gopinath, C.R.; Narasimhamurthy, H.N.; kumar, N. Raja (Journal of Meat Science, 2014)
A study was conducted to evaluate the variations in carcass traits of males, females and on combined sex in indigenous chicken of different districts of Mysore division of Karnataka state. The average live weight recorded was 1136.50±48.26 in Chamarajanagar, 1148.30±81.46 in Mysore and 1262.20±75.92g in Mandya district male birds. The average live weight recorded for female birds was 828.30±70.20 in Mandya, 833.50±53.62 in Mysore and 867.30±77.49g in Chamarajaanagar district. When pooled over sexes the corresponding values for live weight was 990.90±59.64 in Mysore, 1001.90±54.10 in Chamarajanagar and 1045.25±70.75g in Mandya district birds respectively and no significant (P=0.05) differences were noticed between birds of different districts in live weight. In males majority of carcass traits showed significant (P=0.05) differences between different districts except in percent feather weight, heart weight, breast weight, back weight and drumstick weight. In females majority of carcass traits showed no significant (P=0.05) differences between different districts except in percent blood weight, heart weight, giblet weight, breast weight, drumstick weight and thigh weight. When combined over sex, significant (P=0.05) differences were noticed in percent dressed, eviscerated, blood, heart, gizzard, giblet, drumstick, thigh and neck weights. The variations recorded in some carcass traits of males, females and on combined sex of indigenous chicken evaluated in this study could be attributed due to the differences in genetic makeup of the birds of different districts.
Keywords: SIndigenous chicken; Carcass traits; Live weight; Dressed weight